Innovative Surgical Concept for Septic Sternoclavicular Arthritis: Case Presentation of a Simultaneous Joint Resection and Stabilization with Gracilis Tendon Graft Including Literature Review - Hanhoff, Marek; Jensen, Gunnar; Dey Hazra, Rony-Orijit; Lill, Helmut (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Introduction Septic arthritis of the sternoclavicular joint (SCJ) is a rarity in everyday surgical practice with 0.5 – 1% of all joint infections. Although there are several risk factors for the occurrence of this disease, also healthy people can sometimes be affected. The clinical appearance is very variable and ranges from unspecific symptoms such as local indolent swelling, redness or restricted movement of the affected shoulder girdle to serious consequences (mediastinitis, sepsis, jugular vein thrombosis). Together with the low incidence and the unfamiliarity of the disease among practicing doctors in other specialties, this often results in a delay in the diagnosis, which in addition to a significant reduction in the quality of life can also have devastating consequences for the patient.Patient and Method According to a stage-dependent procedure, the therapy strategies range from antibiotic administration only to radical resection of the SC joint and other affected structures of the chest wall in severe cases with the following necessity for flap reconstruction. The aspect of possible post-interventional instability after resection of the SCJ receives little or no attention in the current literature. In the present case report of a 51-year-old, otherwise healthy gentleman with isolated monoarthritis of the right SCJ with Escherichia coli (E. coli) shortly after two prostatitis episodes, the possibility of a new surgical approach with a one-stage eradication and simultaneous stabilization of the SCJ is presented. Therefore, a joint resection including extensive debridement is performed while leaving the posterior joint capsule and inserting an antibiotic carrier. In the same procedure, the SCJ is then stabilized with an autologous gracilis tendon graft by using the “figure of eight” technique, which has become well established particularly for anterior instabilities of the SCJ in recent years.Results and Conclusion One year after operative therapy, the patient presented symptom-free with an excellent clinical result (SSV 90%, CS89 points, CSM 94 points, TF 11 points, DASH 2.5 points). It is concluded that in selected cases with an infection restricted to the SCJ without major abscessing in the surrounding soft tissues, the demonstrated procedure leads to good and excellent clinical results with stability of the joint. If the focus of infection and germ are known, stabilization using an autologous graft can be carried out under antibiotic shielding. To the best of the authorsʼ knowledge, this surgical procedure has not yet been described in the current literature. Depending on the extent of the resection, an accompanying stabilization of the SCJ should be considered to achieve stable conditions and an optimal clinical outcome.Einleitung Septische Arthritiden des Sternoklavikulargelenks (SCG) stellen mit 0,5 – 1% aller Gelenkinfektionen eine Rarität im chirurgischen Alltag dar. Obwohl eine Vielzahl an Risikofaktoren für das Auftreten dieser Erkrankung existiert, können gelegentlich gesunde Menschen daran erkranken. Das klinische Erscheinungsbild präsentiert sich mitunter sehr variabel und reicht von unspezifischen Symptomen bis hin zu schwerwiegenden Folgeerscheinungen (Mediastinitis, Sepsis, Jugularvenenthrombose). Zusammen mit der niedrigen Inzidenz und der Unbekanntheit der Erkrankung bei praktizierenden Ärzten anderer Fachrichtungen resultiert dies nicht selten in einer Verzögerung der Diagnosestellung, was neben einer deutlichen Einschränkung der Lebensqualität u. U. auch verheerende Folgen für den Patienten nach sich ziehen kann.Patient und Methode Gemäß eines stadienabhängigen Vorgehens reichen die Therapiestrategien von der reinen antibiotischen Abschirmung bis hin zu einer radikal-chirurgischen Resektion des Gelenks und anderer betroffener Strukturen der Thoraxwand in schwerwiegenden Fällen mit möglicher Notwendigkeit einer plastischen Deckung. Der Aspekt einer möglichen postinterventionellen Instabilität nach Resektion des SCG findet dabei in der aktuellen Literatur wenig bis keine Beachtung. Im vorliegenden Fallbeispiel eines 51-jährigen, ansonsten gesunden Patienten mit isolierter Monoarthritis des rechten SCG mit Escherichia coli (E. coli) kurze Zeit nach 2-maliger Prostatitis soll die Möglichkeit einer neuen operativen Herangehensweise mit einzeitiger Infektsanierung und gleichzeitiger Stabilisierung des SCG vorgestellt werden. Hierbei wird zunächst eine Gelenkresektion inkl. eines ausführlichen Débridements durchgeführt, wobei die hintere Gelenkkapsel belassen und ein Antibiotikaträger eingelegt wird. Anschließend erfolgt in derselben Prozedur die Stabilisierung des SCG mittels eines autologen Gracilissehnengrafts in der insbesondere für anteriore Instabilitäten etablierten „figure-of-eight“-Technik.Ergebnisse und Schlussfolgerung Ein Jahr nach operativer Therapie präsentiert sich der Patient im Follow-up beschwerdefrei mit einem exzellenten klinischen Resultat (SSV 90%, CS89 Punkte, CSM 94 Punkte, TF 11 Punkte, DASH 2,5 Punkte). Es wird daraus geschlussfolgert, dass das demonstrierte Vorgehen in ausgewählten Fällen mit einer auf das SCG beschränkten Infektion zu guten klinischen Ergebnissen mit stabilen Gelenkverhältnissen führt und bei bekanntem Keim einzeitig unter antibiotischer Abschirmung nach Fokussanierung eine Stabilisierung mithilfe eines autologen Sehnengrafts erfolgen kann. Nach Kenntnis der Autoren wurde dieses chirurgische Vorgehen bis dato in der Literatur noch nicht beschrieben. Abhängig vom notwendigen Resektionsausmaß sollte eine damit einhergehende Stabilisierung des SCG in Betracht gezogen werden, um stabile Verhältnisse und ein optimales Patientenoutcome zu erzielen.
Keywords: SCJ; sternoclavicular joint infection; septic arthritis; SC joint reconstruction; SC joint graft augmentation